IDEOLOGICAL FORMATION IN RONDA DRAMA TEXT BY ATUT ADI BASKORO: ANTONIO GRAMSCI PERSPECTIVE (FORMASI IDEOLOGI DALAM TEKS DRAMA RONDA KARYA ATUT ADI BASKORO: PERSPEKTIF ANTONIO GRAMSCI) - Turmudzi, Muhammad Imam (Universitas PGRI Sumatera Barat, 2019)
This study aims to describe ideological formation and ideological negotiations in the drama text